Therapeutic endoscopy in the gastrointestinal tract - Kähler, Georg; Götz, Martin; Senninger, Norbert (Springer, 2018)
This book, written by experts on gastroenterology and digestive surgery, provides comprehensive and detailed descriptions of all established and newly developed interventional endoscopic procedures. For each procedure, it addresses: indications; staff, instrumental and technical requirements; and results, potential complications and their management. Also featuring a wealth of images and drawings of the procedures, as well as helpful hints and tips, the book offers a valuable resource for young and seasoned internists and surgeons alike, as well as endoscopy specialists in other fields
Keywords: Gastroenterologische Endoskopie